Two C3‐Symmetric Dy3III Complexes with Triple Di‐μ‐methoxo‐μ‐phenoxo Bridges, Magnetic Ground State, and Single‐Molecule Magnetic Behavior. Issue 27 (30th May 2014) - Hänninen, Mikko M.; Mota, Antonio J.; Aravena, Daniel; Ruiz, Eliseo; Sillanpää, Reijo; Camón, Agustín; Evangelisti, Marco; Colacio, Enrique
Abstract Two series of isostructural C3‐symmetric Ln3 complexes Ln3⋅[BPh4] and Ln3⋅0.33[Ln(NO3)6] (in which LnIII=Gd and Dy) have been prepared from an amino‐bis(phenol) ligand. X‐ray studies reveal that LnIII ions are connected by one μ2‐phenoxo and two μ3‐methoxo bridges, thus leading to a hexagonal bipyramidal Ln3O5 bridging core in which LnIII ions exhibit a biaugmented trigonal‐prismatic geometry. Magnetic susceptibility studies and ab initio complete active space self‐consistent field (CASSCF) calculations indicate that the magnetic coupling between the DyIII ions, which possess a high axial anisotropy in the ground state, is very weakly antiferromagnetic and mainly dipolar in nature. To reduce the electronic repulsion from the coordinating oxygen atom with the shortest DyO distance, the local magnetic moments are oriented almost perpendicular to the Dy3 plane, thus leading to a paramagnetic ground state. CASSCF plus restricted active space state interaction (RASSI) calculations also show that the ground and first excited state of the DyIII ions are separated by approximately 150 and 177 cm−1, for Dy3⋅[BPh4] and Dy3⋅0.33[Dy(NO3)6], respectively. As expected for these large energy gaps, Dy3⋅[BPh4] and Dy3⋅0.33[Dy(NO3)6] exhibit, under zero direct‐current (dc) field, thermally activated slow relaxation of the magnetization, which overlap with a quantum tunneling relaxation process. Under an applied Hdc field of 1000 Oe, Dy3⋅[BPh4] exhibits two thermally activated processes with Ueff values of 34.7 and 19.5 cm−1, whereas Dy3⋅0.33[Dy(NO3)6] shows only one activated process with Ueff=19.5 cm−1.